Relationship Between Dietary Omega-3 and Omega-6 Polyunsaturated Fatty Acids Level and Sarcopenia. A Meta-Analysis of Observational Studies - Zhang, Yi; Guo, Hongbin; Liang, Jieyu; Xiao, Wenfeng; Li, Yusheng (Frontiers in Nutrition, 2022)
Objective: This study aims to investigate the relationship between dietary omega-3 and omega-6 polyunsaturated fatty acids (PUFAs) level and sarcopenia. Methods: A comprehensive literature search in the databases of PubMed, Web of Science and Embase (up to July 2021) was conducted to identify the observational studies on the relationship between dietary omega-3 and omega-6 PUFAs level and sarcopenia. The pooled odds ratio (OR) of sarcopenia for the highest versus lowest dietary omega-3 and omega-6 PUFAs level, and the standard mean difference (SMD) of dietary omega-3 and omega-6 PUFAs level for sarcopenia versus control subjects were calculated. Results: A total of 6 studies were identified in this meta-analysis. The overall multi-variable adjusted OR showed that dietary omega-3 PUFAs level was inversely associated with sarcopenia (OR=0.41, 95% CI: 0.26 to 0.65; P=0.0001). Moreover, the overall combined SMD showed that the dietary omega-3 PUFAs level in sarcopenia was lower than that in control subjects (SMD=-0.19, 95%CI: -0.32 to -0.07; P=0.002). With regard to dietary omega-6 PUFAs level, the overall multi-variable adjusted OR suggested no significant relationship between dietary omega-6 PUFAs level and sarcopenia (OR=0.64, 95% CI: 0.33 to 1.24; P=0.19). However, the overall combined SMD showed that the dietary omega-6 PUFAs level in sarcopenia was slightly lower than that in control subjects (SMD=-0.15, 95%CI: -0.27 to -0.02; P=0.02). Conclusion: Our results suggest that the dietary omega-3 PUFAs level is inversely associated with sarcopenia. However, current evidence is still insufficient to demonstrate the definite relationship between dietary omega-6 PUFAs level and sarcopenia. More well-designed prospective cohort studies with the dietary omega-3/omega-6 PUFAs ratio are still needed.